Carbon-Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides - Wiesinger, Michael; Rösch, Bastian; Knüpfer, Christian; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Reaction of [(DIPePBDI)SrH]2 with C6H5X (X=Cl, Br, I) led to hydride-halogenide exchange (DIPePBDI=HC[(Me)CN-2,6-(3-pentyl)phenyl]2). Conversion rates increase with increasing halogen size (F<Cl<Br<I). Reaction of [(DIPePBDI)SrH]2 with C6H5F was slow and ill-defined but addition of C6H4F2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [(DIPePBDI)SrX ⋅ THF]2 (X=F, Cl, Br, I). Mixtures of AeN“2 and PhSiH3 in situ formed less defined but more robust Ae metal hydride clusters (AexN”yHz, Ae=Ca, Sr, Ba and N“=N(SiMe3)2) which are able to hydrodefluorinate C6H5F. Conversion rates increase with increasing metal size (Ca<Sr<Ba). Also alkylfluorides (1-F-hexane, F-cyclohexane, 1-F-adamantane) could be converted but, due to solubility problems of the Ba species, the fastest conversion was found for Sr. These AeN”2/PhSiH3 mixtures also converted SF6 at room temperature to give undefined decomposition products. Addition of Me6Tren to a SrN“2/PhSiH3 led to crystallization of [Sr6N”2H9 ⋅ (Me6Tren)3+][SrN“3−]; Me6Tren=tris[2-(dimethylamino)ethyl]amine). After hydrodefluorination, Sr6N”4F8 ⋅ (Me6Tren)2 was formed and structurally characterized. Dissolution in THF led to cluster growth and the larger cluster Sr16N“8F24 ⋅ (THF)12 is structurally characterized. DFT calculations support that hydrodehalogenation of halobenzenes follows a concerted nucleophilic aromatic substitution mechanism (cSNAr).
CRIS-Team Scopus Importer:2021-08-27
Keywords: Alkaline-earth metal; DFT calculation; Hydride; Hydrodehalogenation